1972
DOI: 10.1139/v72-005
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of some Hydrocarbons in Air: a Regularity in the Diffusion Coefficients of a Homologous Series

Abstract: Diffusion coefficients in air at 298.2 "K and I atm pressure are reported for ethane, ethene, ethyne, cyclopropane, propene, propadiene, propyne, butane, I-butene, 2-methylpropene, cis-2-butene, trans-2-butene, 1,3-butadiene, I-butyne, 2-methylbutane, 2,2-dimethylpropane, cyclopentane, and 1-pentene.A linear relationship, valid for alkanes and alkenes, has been found between the diffusion coefficient and the reduced molecular weight of the members of a homologous series and air.Diffusion coefficients calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

1972
1972
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(24 citation statements)
references
References 6 publications
3
21
0
Order By: Relevance
“…Vesborg et al [17] even found for methanol photooxidation on TiO 2 that photodesorption is more pronounced at longer wavelengths of light, further increasing k À 1 . A diffusion constant of D ¼ 0:17 cm 2 s À1 compares well to literature values of 0.1655 cm 2 s À1 for ethene in air [18]. Data up to a gas velocity of 200 m h À1 are available, but the model fits are extrapolated to higher velocities where the model ensures that the correct limit in output concentration is reached -never surpassing the input concentration.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Vesborg et al [17] even found for methanol photooxidation on TiO 2 that photodesorption is more pronounced at longer wavelengths of light, further increasing k À 1 . A diffusion constant of D ¼ 0:17 cm 2 s À1 compares well to literature values of 0.1655 cm 2 s À1 for ethene in air [18]. Data up to a gas velocity of 200 m h À1 are available, but the model fits are extrapolated to higher velocities where the model ensures that the correct limit in output concentration is reached -never surpassing the input concentration.…”
Section: Resultssupporting
confidence: 78%
“…Ethene emission as a function of ethene concentration in the surrounding air, evaluated through Eq. (18). Km is the concentration of half maximum response, and p max is the maximum production rate at infinite input concentration CB.…”
Section: Shipping Container Parametersmentioning
confidence: 99%
“…Fitting the data with Eqs. (7) and (8), taking ˇ= 1.61 cm −1 , one calculates a diffusion coefficient of 0.030 cm 2 /s for pentane in helium, while the value reported in the literature is 0.092 cm 2 /s [17]. The difference may be explained by the approximation of the vapor zone by a Gaussian, which actually is far from being the case, as shown in the inset of Fig.…”
Section: Zone Spreading and The Coefficient Of Diffusionmentioning
confidence: 88%
“…• C. Data for the vapour-air diffusion coefficient D were obtained from various references (Cummings & Ubbelohde 1953;Altshuller & Cohen 1960;Lugg 1968;Elliott & Watts 1972;Beverley, Clint & Fletcher 1999) and extrapolated to 22 ± 1…”
Section: Protocol For a Drying Experimentsmentioning
confidence: 99%